Pentingnya Membangun Kesadaran Mahasiswa Terhadap Moderasi Beragama (Studi Kasus Mahasiswa UIN FAS Bengkulu) - Puspitadewi, Lidiana; Saputra, Zolan; Rismawati, Siti; Nabila, Wika (DAWUH : Islamic Communication Journal, 2022)
Basically, the role of religious moderation is needed in dealing with and preventing conflicts between religious communities, the growth of intolerance and radicalism and preventing acts of violence to create a peaceful state and religious life. As the function of religious moderation that has a role in dealing with pluralistic culture, religious moderation is the most powerful weapon to defeat so that radicalism does not occur, conflict is through moderate and comprehensive Islamic teachings. This research uses a qualitative approach, namely research that produces descriptive data in the form of descriptions of written or spoken words obtained from people and from observed behavior. The type of research used in this research is a case study. This case study research centers on one object intensively and studies it as a case. In this research, the case study is students of Fatmawati Sukarno State Islamic University Bengkulu. Religious moderation can be done by understanding the main teachings of religion well, namely upholding human values. No one teaches to be too extreme and act for violence and spread hatred. Islam also teaches about the values of kindness and peace, if a teaching is found that is far from the discussion of humanity and tolerance, then it can be said to be extreme teaching. Therefore, it can be concluded that religious moderation is a way of seeing and behaving someone in the middle position, not heavy to the right or left in embracing religion, so that it is not extreme or excessive. By realizing religious moderation, then in living together and a multicultural society, a harmonious, safe and peaceful life will be achieved.